Oracle business intelligence Discoverer 11g handbook - Armstrong-Smith, Michael; Armstrong-Smith, Darlene (McGraw-Hill Education, 2014)
Provide secure, immediate access to critical business information from relational and multidimensional data sources across your organization. Optimize this intuitive ad hoc query, reporting, analysis, and web publishing tool for maximum performance. Real-world examples illustrate the powerful analysis, security, and reporting capabilities. Enable business users at all levels to make faster, more-informed decisions with help from this Oracle Press guide--Cover.